DEVELOPING A DIGITAL VIDEO SERIES TO ENHANCE MEDICAL ENGLISH SPEAKING PROFICIENCY - Sulistiana, Eva; Adianto, Arda; Nadzifah, Wardatun (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study investigates the design, development, and implementation of a Digital Video Series (DVS) aimed at enhancing Medical English speaking proficiency among health-science students. Using a Research and Development (RD) approach adapted from the Borg and Gall model, the study followed seven systematic stages including needs analysis, planning, product development, expert validation, field testing, and final revision. A one-group pre-test–post-test design was employed with 109 Nursing, Midwifery, and Pharmacy students to measure speaking improvement after the implementation of the DVS, which features authentic clinical communication scenarios. The results demonstrated a substantial increase in speaking performance, with mean scores rising by 13.49 points and a statistically significant difference confirmed through a paired-sample t-test (p .001). Students also reported highly positive perceptions of the videos’ clarity, relevance, and usefulness for supporting communicative practice. Overall, the study provides empirical evidence that systematically developed video-based materials can effectively strengthen communicative competence in English for Medical Purposes (EMP). The DVS offers a feasible and contextually grounded model for integrating multimedia learning resources into EMP curricula, particularly in settings with limited access to authentic clinical exposure.